2005
DOI: 10.1136/pgmj.2004.029074
|View full text |Cite
|
Sign up to set email alerts
|

The heart and the oesophagus: intimate relations

Abstract: The close anatomical relations of the heart and oesophagus, and the similarity of symptoms attributable to disorders of either organ, often lead to diagnostic difficulty in patients with chest pain. A definitive diagnosis of non-cardiac chest pain attributable to oesophageal reflux or spasm is hampered, both by the need for prolonged ambulatory monitoring of pH, manometry, and endoscopy, and by the common occurrence of asymptomatic reflux and spasm, and the corresponding difficulty in linking an episode of ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…In the medical literature there are cases of swallowinginduced arrhythmias but the mechanism of induction in our case seems to be opposite to that [4,5]. In contrast to swallowing-induced bradyarrhythmias, most of the cases of swallowing-induced tachyarrhythmias have not been associated with esophageal or cardiac disorders.…”
Section: Discussioncontrasting
confidence: 71%
“…In the medical literature there are cases of swallowinginduced arrhythmias but the mechanism of induction in our case seems to be opposite to that [4,5]. In contrast to swallowing-induced bradyarrhythmias, most of the cases of swallowing-induced tachyarrhythmias have not been associated with esophageal or cardiac disorders.…”
Section: Discussioncontrasting
confidence: 71%
“…23 However, confirmation of GORD as the cause of non-specific chest pain in individual patients is often difficult and may need expensive, prolonged pH-monitoring or manometry. 15,24,25 In this study, among those patients not previously consulting for reflux symptoms, there was a greater than fourfold increased risk of developing GORD or dyspepsia after the initial consultation for nonspecific chest pain. Furthermore, it has been shown that, among those untreated at the index date, patients with non-specific chest pain were much more likely than controls to begin new treatment with PPIs, which is likely to be a reflection of new GORD diagnoses.…”
Section: Comparison With Existing Literaturementioning
confidence: 89%
“…However, many patients with angina-like chest pain and no response to proton pump inhibitors have a completely normal exercise ECG and are therefore not subjected to coronary angiography, particularly if they are relatively young and have no other risk factors. Similarly, they are not routinely subjected to investigation of oesophageal motility or sensitivity as it is felt by some that the correlation with symptoms is not especially good [10][11][12] and that the available pharmacological approaches are not sufficiently sophisticated to target such abnormalities, even if they are identified.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between manometric events as well as other tests of oesophageal function and symptoms is variable [10][11][12] although probably the most consistent association is with oesophageal reflux. 13 14 Clinical trials of proton pump inhibitors have shown a positive effect 15 and it has even been suggested that administration of such a medication could be used as a diagnostic test [16][17][18] for confirming the role of reflux in the symptoms of a particular individual.…”
mentioning
confidence: 99%